Repressive Coping Does Not Contribute to Anosognosia in First-Diagnosis Patients With Alzheimer Disease. (July 2017) - Verhülsdonk, Sandra; Lange-Asschenfeldt, Christian; Höft, Barbara; Schwender, Holger; Supprian, Tillmann; Hellen, Florence; Kalbe, Elke
Abstract : Anosognosia is common in patients with Alzheimer disease (AD) even in early stages. Although neural correlates and the impact of cognitive dysfunctions have been described, possible psychodynamic processes such as a repressive coping style as described in other illnesses, have not been examined. Our study aimed to examine possible psychological influence factors on illness perception embracing a repressive coping style and cognitive functions in AD patients in the diagnostic process. Fifty-four subjects with mild AD diagnosed in our memory clinic were enrolled. Anosognosia was evaluated using a patient-caregiver discrepancy rating. All patients underwent comprehensive neuropsychological testing. In addition, characteristics of a repressive coping style were assessed. In total, 79.6% of our patients showed a lack of awareness at least to some degree. 33.3% of the patients were classified as repressors. Repressors and nonrepressors did not differ in cognition, or the unawareness score. Multivariate regression analysis showed that repressive coping style did not significantly contribute to anosognosia, but that verbal memory and naming ability had a strong influence. Although our data indicate that a high proportion of patients with mild AD show characteristics of repressive coping, this possible defense mechanism had no influence on the awareness of illness-related deficits measured by caregiver patient discrepancy.